Architecture for Location Independent CORBA Environments - Cunningham, Raymond (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 1998)
The construction of distributed applications is a complex and time consuming task, which has been addressed by the Object Management Group's Common Object Request Broker Architecture. However implementations of this standard are typically designed for stationary hosts connected to a fixed network and do not take into account the problems associated with mobile computing. These problems include limited processing resources on the mobile host and the use of unreliable and low-bandwidth wireless networks. A full CORBA implementation is unsuitable for use on mobile hosts, such as laptops and personal digital assistants, since it is too resource intensive. It is however desirable for mobile hosts to be able to interopate with existing CORBA applications while simultaneously taking advantage of mobility. This dissertation describes the design and implementation of a collection of components suitable for building applications, which are capable of interoperating with CORBA implementations and which are suitable for mobile hosts. The collection of components allows an application to act as a client or as a server in a CORBA context. The implementation was carried out on Windows NT and Solaris using C and C++, Windows and Unix Sockets are used for network communication.
Keywords: Computer Science, M.Sc; M.Sc. Trinity College Dublin